Fluorescence sensing of nitro-aromatics by Zn(ii) and Cd(ii) based coordination polymers having the 5-[bis(4-carboxybenzyl)-amino]isophthalic acid ligand. (12th April 2017) - Lu, Lu; Wang, Jun; Xie, Bin; Liu, Jian-Qiang; Yadav, Reena; Singh, Amita; Kumar, Abhinav
Abstract : Three new d 10 based MOFs using 5-[bis(3-carboxybenzyl)-amino]isophthalic acid were synthesized and their sensing behavior towards nitroaromatics was evaluated. Abstract : Three new coordination polymers (CPs) viz. [Zn2 (L)] n (1 ), {[Cd3 (L)2 (H2 O)][Na2 (μ2 -H2 O)(H2 O)7 ]} n (2 ) and [Zn2 (L)(phen)2 (H2 O)·H2 O] n (3 ) were synthesized by the reaction between 5-[bis(3-carboxybenzyl)-amino]isophthalic acid (H4 L) Zn(NO3 )2 (1 )/Cd(NO3 )2 (2 ) or Zn(NO3 )2 and H4 L in the presence of 1, 10-phenanthroline (phen) (3 ) and characterized. X-ray single-crystal analyses reveal that1 possesses a 3D architecture with a {4·6 2 }{4·8 2 }{4 2 ·6 5 ·8 8 } topology, whereas2 shows a unique (4, 8)-connected 3D framework with a {4 11 ·6 15 ·8 2 }{4 5 ·6}{4 6 } topology. In the case of3, the L and phen ligands linked the Zn(ii ) atoms into a deeply corrugated 2D sheet. The results showed that the structural diversity of the polymers resulted from the different geometries of the metal ions and the effect of the assistant ligands. The photoluminescence sensing of nitro-aromatics by1–3 indicates that these CPs could be prospective candidates for developing luminescence sensors for selective sensing of these species. Theoretical and experimental investigations indicate that the observed quenching in the photoluminescence intensities of1–3 by nitro-aromatics may be assigned to the occurrence of both electron and energy transfer processes, in addition to electrostatic interaction between the CPs and nitro-aromatics.